Determinants of species rarity: population growth rates of species sharing the same habitat - Münzbergová, Zuzana (American journal of botany, 2005)
Determining differences between common and rare species is commonly used to identify factors responsible for rarity. Existing studies, however, suffer from two important drawbacks. First, studies compare species that are closely related phylogenetically but occupy different habitats. Second, these studies concentrate on single life history traits, with unknown relevance for population growth rates. Complete life cycles of one rare and one common Cirsium species sharing the same habitat were compared. Population growth rate was slightly lower in the rare species, translating into a large difference in local extinction probability. Seed predation intensity did not differ between species. However, it can be demonstrated that in connection with the data on complete demography, seed predation is the key factor causing a lower population growth rate in the rare species. These results are the first estimation of factors responsible for commonness or rarity of plants in terms of population growth rate without confounding differences in ecology. They demonstrate that conclusions based on single traits may be misleading and that only a comparison based on a complete life cycle can provide unequivocal evidence for concluding which factors are really those responsible for species commonness or rarity.